Arbitrase Sebagai Alternatif Penyelesaian Perkara dalam Hukum Positif dan Hukum Islam - Atful Munawar (Kosmik Hukum, 2022)
The sharia-based economy in Indonesia has experienced significant development. Along with the growth of the sharia economy, the emergence of disputes between the parties to the transaction is also increasing. On the other hand, resolving disputes through the courts requires a lot of time and money. Thus, alternative dispute resolution (APS) emerged, one of which was arbitration. This study aims to describe the concept of arbitration in positive law and tahkim in Islamic law. This research is a qualitative research using library research. This study uses a normative juridical approach. The results of the study show that arbitration and tahkim are both alternative dispute resolutions by appointing a third party as arbitrator or judge. The difference is in the requirements to become an arbitrator / judge where in Islamic law there is a requirement to be Muslim. Regarding its authority, arbitration is only authorized in the civil sector based on an arbitration agreement, while in tahkim its authority is broader in terms of muamalah, social and even political. Another difference is that in positive law the court is only authorized to execute the arbitration award if requested by one of the parties. Meanwhile, in Islamic law, the court has the authority to cancel the decision of the tahkim if it is contrary to the provisions of syara'.Keywords: tahkim, civil disputes, sharia economics